2016
DOI: 10.1007/s10973-016-5555-y
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric and spectroscopic binding studies of amoxicillin with human serum albumin

Abstract: Amoxicillin is a common antibiotic drug used for preventing bacterial colonization of urinary and skin infections. The binding of amoxicillin (AX) to human serum albumin (HSA) in sodium phosphate buffer solution at pH 7.4 has been investigated by UV-visible spectroscopy, fluorescence spectroscopy, Förster resonance energy transfer, isothermal titration calorimetry (ITC), circular dichroism (CD) and FTIR spectroscopy. The binding studies using ITC revealed that the interaction is entropy driven rather than enth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Previous molecular dynamics (MD) and spectroscopic studies have shown that the major driving forces for the interaction between drugs and BSA are electrostatic force and hydrogen bonding. During the binding process, the original hydrogen bonds are disrupted, which uncoiled the α-helices [25,26,31,32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous molecular dynamics (MD) and spectroscopic studies have shown that the major driving forces for the interaction between drugs and BSA are electrostatic force and hydrogen bonding. During the binding process, the original hydrogen bonds are disrupted, which uncoiled the α-helices [25,26,31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Different volumes (30 µL, 60 µL and 90 µL) of the drug solution at a concentration of 2.0 × 10 −5 mol/L were added to 3 mL of BSA, respectively. Next, the protein solutions were left to stand for 5 min to reach dynamic equilibrium [25,26,27].…”
Section: Methodsmentioning
confidence: 99%
“…Each domain is further divided into two subdomains (A and B) with numerous requisite ligands. 2 Aer the entry of a drug into systemic circulation, it is exposed to serum albumin, leading to the division of the drug into two types: free drug and drug-HSA complexes. This drug-HSA complex formed provides the supply of free drug and extends the duration of the drug's action.…”
Section: Introductionmentioning
confidence: 99%
“…In the presented work, two complementary techniques, namely differential scanning calorimetry (DSC) and isothermal titration calorimetry (ITC), have been employed to study physicochemical properties of the LL-37 peptide. These techniques are generally used for the characterization of the peptides in aqueous solution [12][13][14].…”
Section: Introductionmentioning
confidence: 99%